2023
DOI: 10.2196/40421
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Brain Activity and Body Movements Between Virtual Reality and Offline Exercise: Randomized Crossover Trial

Abstract: Background Virtual reality (VR) has been suggested to be effective at enhancing physical exercises because of its immersive characteristics. However, few studies have quantitatively assessed the range of motion and brain activity during VR exercises. Objective We hypothesized that 3D immersive VR could stimulate body movement and brain activity more effectively than standard exercises and that the increased range of motions during 3D immersive VR exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“… 81 Several iVR-fNIRS studies have implemented fully immersive virtual environments and stimulations that could span over multiple dimensions to modify subjects’ visual, auditory, haptic, and other sensory inputs, inducing illusions of flying, driving, out-of-body experiences, or emergency situations. 43 , 53 , 61 , 66 Another application is the study of brain responses during exposure therapy for individuals with phobia or anxiety disorders. 60 iVR allowed for complex object/situation presentations while offering precise adjustments on exposure type, duration, and dose, overcoming the current barrier of ethical or tolerability concerns in such studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 81 Several iVR-fNIRS studies have implemented fully immersive virtual environments and stimulations that could span over multiple dimensions to modify subjects’ visual, auditory, haptic, and other sensory inputs, inducing illusions of flying, driving, out-of-body experiences, or emergency situations. 43 , 53 , 61 , 66 Another application is the study of brain responses during exposure therapy for individuals with phobia or anxiety disorders. 60 iVR allowed for complex object/situation presentations while offering precise adjustments on exposure type, duration, and dose, overcoming the current barrier of ethical or tolerability concerns in such studies.…”
Section: Discussionmentioning
confidence: 99%
“… 105 Addressing these challenges is crucial in future iVR-fNIRS investigations to ensure the reliability of findings and prevent false discoveries. 110 Strategies employed in the reviewed studies included adopting lower low-pass temporal filtering cutoff frequencies (e.g., 0.1 or 0.2 Hz) 28 , 32 , 42 , 44 47 , 51 , 53 , 55 , 60 , 61 in contrast to the recommended 0.5Hz, 111 various motion correction methods, 35 , 38 , 39 , 44 , 55 , 56 , 62 principal component analysis for signal component separation, 57 , 61 and pre-whitening and least-square regression-based approaches to eliminate intrinsic signal auto-correlations. 33 , 54 , 58 , 59 Some studies incorporated additional measures to account for systemic physiological effects, such as the inclusion of short-separation fNIRS channels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were included if they were male Korean nationals aged ≥20 years attending university with a major in physical education; participants' physical health, along with confirmation of an absence of mental illness, was confirmed by a health check-up program at a university-affiliated hospital. Participants were excluded if they had a history of head trauma; abused substances such as alcohol, tobacco, or drugs; were unable to understand the study and consent procedures; or had a confirmed diagnosis of a mental or psychiatric disorder [20]. For this study, we estimated the sample size using G* Power (Heinrich-Heine-Universität).…”
Section: Study Design and Participantsmentioning
confidence: 99%